Land Use Change using Geospatial Techniques: The Case of Awoja Watershed in Ngora District in Eastern Uganda - Akello, Sarah; Turyahabwe, Nelson; Okullo, Paul; Agea, Jacob Godfrey (Uganda Journal of Agricultural Sciences, 2018)
This study used remote sensing and Geo-graphical Information System (GIS) to assess the status of Awoja watersheds in Ngora district of Eastern Uganda. Landsat ETM Images covering the whole of Ngora district and part of Lake Kyoga of two time periods was carried out in the period April to July 2015. This was acquired using USGS Earth Explorer. The images were processed and enhanced with ERDAS 2014 software to aid information extraction and analysis. Land cover change analysis was performed using ENVI 5.3 software. Supervised classification method with maximum likelihood algorithm was performed to obtain land use/ cover types. Five land use/cover types were identified: open water, wetland, tree cover, agriculture and built up area. The findings indicate a fivefold increase in built up area by 154.27km2 (i.e. 375%) and open water increased by 8.7 km2 (i.e. 55.33%). Wetland, tree cover and agriculture reduced in area by -1.0km2 (i.e. 5.1%), - 48.07 km2 (i.e. 34.46%) and -114.0km2 (i.e. 51.05%), respectively. These changes mainly resulted from deforestation, wetland encroachment, poor attitude and over population. Unless, appropriate watershed restoration strategies are designed through afforestation, law enforcement on culprits, continuous sensitisation of the watershed community on the causes of degradation, the over 1,700,000 individuals whose livelihoods depend on Awoja will continue to suffer the effects of degradation. There is need to advocate for non-consumptive projects as alternative sources of income.
Keywords: Remote sensing; GIS; Watersheds